Analysis of File Carving Approaches : A Literature Review - NOR IKA SHAHIRAH, RAMLI; SYIFAK IZHAR, HISHAM; GRAN, BADSHAH (2021)
Home Advances in Cyber Security Conference paper Analysis of File Carving Approaches: A Literature Review Nor Ika Shahirah Ramli, Syifak Izhar Hisham & Gran Badshah Conference paper First Online: 01 January 2022 1262 Accesses